(untitled) (Pedagogy of Higher and Secondary Education, 2007)
The article analysis the specifics of teaching musical falklore and study of falk-lore in the system of higher musical education of Ukraine (the Academies of Music, Music Pedagogical Departments of Teacher’s Training Universities, Universities of Culture and Arts). On the basis of the analyses of higher musical establishments curricula and syllabi the pedagogical aspect of musicologist and specialists in folklore training is revealed. It is emphasized that the musical and study of falk-lore education fixedly occupied a fitting place in the system of musical pedagogics, the speciality “Musical Falk-Lore” firmly established and is provided by the series of twenty special subjects.